Modulating the inflammatory properties of activated microglia with Docosahexaenoic acid and Aspirin - Pettit, Lauren K (BioMed Central, 2013)
BACKGROUND: Microglia are considered the “resident macrophages” of the brain. When in their resting state, microglia perform routine maintenance and immune surveillance. Once activated, either by injury or an immune stimulus, microglia secrete a variety of pro-inflammatory molecules, such as Nitric Oxide, superoxide, and inflammatory cytokines. Up-regulation of pro-inflammatory molecules is transient, and does not cause neurodegeneration. However, if up-regulation lasts for an extended period of time, neurodegeneration ensues. Many neurodegenerative diseases are characterized by chronic inflammation due to microglial activation. Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) have been proposed as possible preventative treatments for neurodegenerative diseases, due to their anti-inflammatory properties. Docosahexaenoic Acid (DHA) is an omega-3 polyunsaturated fatty acid (PUFA) that has potent anti-inflammatory properties.This research work sought to elucidate whether microglial activation can be modulated by combining Aspirin, a classical NSAID, with Docosahexaenoic Acid, a natural anti-inflammatory agent. The combined ability of Aspirin and DHA to modulate microglial activation was determined in the context of pro-inflammatory cytokines, Nitric Oxide levels, as well as total Glutathione levels. RESULTS: Docosahexaenoic Acid increased total Glutathione levels in microglia cells and enhanced their anti-oxidative capacity. It reduced production of the pro-inflammatory cytokines TNF-α and IL-6 induced through TLR-3 and TLR-4 activation. Furthermore, it reduced production of Nitric Oxide. Aspirin showed similar anti-inflammatory effects with respect to TNF-α during TLR-3 and TLR-7 stimulation. Aspirin did not show any redection in terms of Nitric Oxide production. Combination of Aspirin and Docosahexaenoic Acid showed augmentation in total Glutathione production during TLR-7 stimulation as well as a reduction in IL-6, TNF-α and Nitric Oxide. CONCLUSIONS: Collectively, these findings highlight the combination of Docosahexaenoic Acid and Aspirin as a possible measure against inflammation of the nervous system, thus leading to protection against neurodegenerative diseases with an inflammatory etiology.